PENGARUH KEGIATAN PERCOBAAN SAINS TERHADAP KEMAMPUAN KOGNITIF ANAK USIA 5-6 TAHUN DI RA AL HIDAYAH - Khoirul Umiah; Pujianti, Yuli; Sofia Trisna Sazain; Edy Mustofa (Al Hanin, 2023)
ABSTRACT Cognitive abilities of children aged 5-6 years at RA Al Hidayah have not developed properly, so there needs to be efforts to develop cognitive abilities. This study aims to obtain empirical data regarding the effect of science experiment activities on the cognitive abilities of children aged 5-6 years at RA Al Hidayah Bekasi. The research method used is a quantitative method of experimental type. The research design used a true experimental design with a posttest-only control design technique. The posttest-only control design is an experimental research design in which two groups are selected randomly, the first group being treated and the other group not being given any treatment. The data collection method used an observation sheet in the form of a checklist that measures the cognitive abilities of children aged 5-6 years. The results of the post-test data analysis showed that the level of cognitive development of children who were treated with science experiment activities was higher than the group of children who were not treated with science experiment activities. This is evidenced by the average value of the post test results between the experimental group of 45.33 which is higher than the control group of 39.86, with a significant difference of 5.46. The results of hypothesis testing using a t-test that compares the average post-test score between the experimental group and the control group obtained the value of tcount = 2.610 and Sig. (2-tailed) = 0.014, with ttable = 2.16. Because the value of tcount is greater than ttable and the value of Sig. (2-tailed) is less than 0.05, then "Ha is accepted". The conclusion of the study is that there is a positive and significant effect of science experiment activities on the cognitive abilities of children aged 5-6 years at RA Al Hidayah. ABSTRAK Kemampuan kognitif anak usia 5-6 tahun di RA Al Hidayah belum berkembang sebagaimana mestinya, sehingga perlu ada upaya untuk mengembangkan kemampuan kognitif. Penelitian ini bertujuan untuk mendapatkan data empirisi mengenai pengaruh kegiatan percobaan sains terhadap kemampuan kognitif anak usia 5-6 tahun di RA Al Hidayah Bekasi. Metode penelitian yang digunakan adalah metode kuantitatif jenis eksperimen. Desain penelitian menggunakan desain penelitian sebenarnya (true experimental design) dengan teknik posttest-only control design. Posttest-only control design adalah desain penelitian eksperimen dengan terdapat dua kelompok yang dipilih secara random, kelompok pertama diberi perlakuan dan kelompok yang lain tidak diberikan perlakuan. Metode pengumpulan data menggunakan lembar observasi berupa ceklis yang mengukur kemampuan kognitif anak usia 5-6 tahun. Hasil penelitian analisis data post test diketahui tingkat perkembangan kognitif anak yang diberi perlakuan kegiatan percobaan sains lebih tinggi dibandingkan kelompok anak yang tidak diberi perlakuan kegiatan percobaan sains. Hal ini terbukti dengan nilai rata-rata hasil post test antara kelompok eksperimen sebesar 45,33 yang lebih tinggi dibandingkan kelompok kontrol sebesar 39,86, dengan perbedaan yang cukup signifikan sebesar 5,46. Hasil uji hipotesis menggunakan uji t yang membandingkan skor rata-rata post test antara kelompok eksperimen dengan kelompok kontrol diperoleh nilai thitung = 2,610 dan Sig. (2-tailed) = 0,014, dengan ttabel = 2,16. Karena nilai thitung lebih besar dari ttabel dan nilai Sig. (2-tailed) lebih kecil dari 0,05, maka ”Ha diterima”. Kesimpulan penelitian adalah terdapat pengaruh positif dan signifikan kegiatan percobaan sains terhadap kemampuan kognitif anak usia 5-6 tahun di RA Al Hidayah.